The Study of Notes and Notebooks: Some Epistemological and Ontological Issues - CRIȘAN, Anton (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
The aim of the present paper is to situate the recent attempts devoted to the study of the phenomena of knowledge management in a larger epistemological context. More precisely, I intend to ascertain the entire affair from the perspective of the philosophy of the humanities. This involves understanding it as an endeavor concerned with the search for regularities. As a result, key notions figuring in the repertoire of this kind of undertaking, primarily those of notes and notebooks, are scrutinized for the purpose of revealing their theoretical function. This points towards some ontological issues, such as the idea of taking notes as cultural kinds, namely something analogous to the idea of natural kinds.